2019
DOI: 10.1186/s12871-019-0820-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of sevoflurane or propofol anesthesia on the regional cerebral oxygen saturation in patients undergoing carotid endarterectomy: a prospective, randomized controlled study

Abstract: Background The monitoring of regional cerebral oxygen saturation (SrO 2 ) using near-infrared spectroscopy is useful method to detect cerebral ischemia during. Sevoflurane and propofol decrease cerebral metabolic rate (CMRO 2 ) in a similar manner, but the effects on the cerebral blood flow (CBF) are different. We hypothesized that the effects of sevoflurane and propofol on SrO 2 were different in patients with defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…The mean rScO 2 was similar between the ipsilateral and contralateral hemispheres from induction until carotid artery clamping. Similar to earlier results, the decrease in mean rScO 2 noted in the present work was significantly different between the two hemispheres (18,30). rScO 2 values were significantly lower in the sevoflurane group than in the propofol group before extubation in the ICU and in female patients than in male patients in the propofol group during cross-clamping.…”
Section: █ Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mean rScO 2 was similar between the ipsilateral and contralateral hemispheres from induction until carotid artery clamping. Similar to earlier results, the decrease in mean rScO 2 noted in the present work was significantly different between the two hemispheres (18,30). rScO 2 values were significantly lower in the sevoflurane group than in the propofol group before extubation in the ICU and in female patients than in male patients in the propofol group during cross-clamping.…”
Section: █ Discussionsupporting
confidence: 91%
“…Previous RCTs comparing the effects of propofol and sevoflurane anesthesia among non-vascular surgery patients suggested that sevoflurane is better than propofol for maintaining cerebral oxygen balance (12,20). In contrast to these studies, Park et al showed that propofolremifentanil anesthesia is comparable with sevofluraneremifentanil anesthesia in preserving cerebral oxygen balance in patients undergoing carotid endarterectomy with carotid cross-clamping, as assessed by NIRS (30). Our results support the findings of Park et al and revealed a statistically significant difference in cerebral oximetry values between male and female patients receiving propofol anesthesia during cross-clamping of the carotid artery.…”
Section: █ Discussionmentioning
confidence: 99%
“…Sevoflurane decreases cerebral blood flow (CBF) at concentrations <1 minimum alveolar concentration (MAC) but increases CBF at concentrations >1 MAC, while propofol decreases CBF in a dose-dependent manner. [ 14 ] Marianna et al showed that sevoflurane anesthesia at 1 MAC can preserve cerebral autoregulation and CO 2 reactivity. [ 15 ] Intravenous anesthesia with propofol has the potential to provide brain protection and preserve regional CBF (rCBF) in the frontal lobes in revascularization surgery for MMD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] A prospective randomized controlled study by Park demonstrated that propofol-remifentanil anesthesia was comparable to sevoflurane-remifentanil anesthesia in terms of preserving regional cerebral oxygen saturation in patients undergoing carotid endarterectomy. [ 14 ] Overall, there is not enough evidence associating the use of a particular maintenance agent with better outcomes in patients with MMD. Further multicenter randomized controlled trials need to be done to establish which anesthetic agent is best for adult patients with MMD.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical signs, such as heart rate (HR) and blood pressure, are unreliable when evaluating an anaesthetic depth and preventing intraoperative awareness. [ 6 8 ] Moreover, early attempts were made to monitor the depth of anaesthesia using electroencephalography, [ 9 ] the entropy index, [ 10 ] cerebral oxygen saturation, [ 11 ] and end-tidal concentrations of inhaled anaesthetics. [ 12 ] However, these indicators have limitations.…”
Section: Introductionmentioning
confidence: 99%